Food safety management a practical guide for the food industry - Motarjemi, Yasmine; Lelieveld, Huub (Academic Press, 2014)
This book presents an integrated, practical approach to the management of food safety throughout the production chain.
Keywords: Food industry and trade -- Safety measures.; Food -- Safety measures.; Food contamination -- Prevention.; elektronické knihy; electronic books